(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
The low effectiveness of conventional physics instruction in enhancing students’ conceptual understanding and engagement has become a major challenge in higher education physics learning. Therefore, this study aims to analyze patterns of innovation in digital-era physics learning and examine their implications for pedagogical practice, educational policy, and future research directions. This study employed a qualitative literature review approach by examining scholarly articles indexed in Scopus, Web of Science, and Google Scholar published between 2019 and 2025, which were analyzed using thematic analysis. The synthesis results indicate that dominant innovation patterns include the implementation of flipped and blended learning, the use of virtual laboratories and digital simulations, and the integration of AI-based adaptive technologies and AR/VR learning environments. Based on the literature synthesis, these digital learning innovations have been reported to improve student learning outcomes by approximately 20–30%, while also enhancing motivation, learning autonomy, and critical thinking skills. Overall, this review emphasizes that digital innovation in physics learning functions not merely as a supplementary tool but as a conceptual foundation for developing a sustainable, data-driven, and future-oriented physics education ecosystem. Accordingly, this study contributes to the scholarly discourse by mapping the direction of pedagogical transformation in higher education physics learning.